[(-3) + (-12)] + (-77) = __________+[(-12) + (-77)]

Question

[(-3) + (-12)] + (-77) = __________+[(-12) + (-77)]

in progress 0
Abigail 1 month 2021-08-16T05:38:18+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-16T05:39:53+00:00

    Answer:

    (3) is the answer

    hope it helps

    0
    2021-08-16T05:40:05+00:00

    Answer:

    [(-3) + (-12)] + (-77) =(3) +[(-12) + (-77)]

    Hope it helps

    Mark upper answer as brainliest

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )